Tree species community spatial structure in a terra firme Amazon forest, Brazil - Silva, Kátia Emidio da; Martins, Sebastião Venâncio; Fortin, Marie-Josee; Ribeiro, Milton Cezar [UNESP]; Azevedo, Celso Paulo de; Ribeiro, Carlos Antonio Álvares Soares; Santos, Nerilson Terra (Universidade Austral de Chile, Faculdade de Ciências Forestais, 2014)
All trees with diameter at breast height dbh >= 10.0 cm were stem-mapped in a "terra firme" tropical rainforest in the Brazilian Amazon, at the EMBRAPA Experimental Site, Manaus, Brazil. Specifically, the relationships of tree species with soil properties were determined by using canonical correspondence analyses based on nine soil variables and 68 tree species. From the canonical correspondence analyses, the species were grouped into two groups: one where species occur mainly in sandy sites, presenting low organic matter content; and another one where species occur mainly in dry and clayey sites. Hence, we used Ripley's K function to analyze the distribution of species in 32 plots ranging from 2,500 m(2) to 20,000 m(2) to determine whether each group presents some spatial aggregation as a soil variations result. Significant spatial aggregation for the two groups was found only at over 10,000 m(2) sampling units, particularly for those species found in clayey soils and drier environments, where the sampling units investigated seemed to meet the species requirements. Soil variables, mediated by topographic positions had influenced species spatial aggregation, mainly in an intermediate to large distances varied range (>= 20 m). Based on our findings, we conclude that environmental heterogeneity and 10,000 m(2) minimum sample unit sizes should be considered in forest dynamic studies in order to understand the spatial processes structuring the "terra firme" tropical rainforest in Brazilian Amazon.

Fueron mapeados los árboles con diámetro a la altura del pecho ≥ 10,0 cm en un bosque tropical lluvioso “terra firme” de la amazonía brasileña, en el Sitio Experimental de EMBRAPA, Manaus, Brasil. Las relaciones de 68 especies arbóreas con las propiedades del suelo fueron determinadas mediante análisis de correspondencia canónica sobre la base de nueve variables del suelo. En este análisis, las especies fueron agrupadas en dos grupos: uno, donde estas crecen principalmente en arena, con suelos de bajo contenido de materia orgánica, y otro, con especies que se desarrollan principalmente en suelos secos y arcillosos. La función K de Ripley fue utilizada para analizar la distribución de las especies en 32 parcelas de 2.500 hasta 20.000 m2 , con el fin de determinar si cada grupo presenta cierto grado de agregación espacial como resultado de variaciones del suelo. Una agregación espacial significativa para los dos grupos solo se encontró en unidades de muestreo > 10.000 m2 , en particular, para especies en suelos arcillosos y ambientes más secos, en los que las unidades de muestreo parecían cumplir con los requisitos de las especies. Variables del suelo, mediadas por la posición topográfica, influyeron la agregación espacial de especies, principalmente en la gama de distancias intermedia a grande (≥ 20 m). Según los resultados, se concluye que la heterogeneidad ambiental y tamaños de unidades de muestreo de por lo menos 10.000 m2 se deben considerar en los estudios de dinámica de bosques con el fin de entender los procesos espaciales que estructuran la selva tropical “terra firme” en la amazonía brasileña.
Estructura espacial de la comunidad de especies arbóreas en el “terra firme”, selva amazónica, Brasil
Keywords: Canonical correspondence analysis; Ripley's K; Spatial point pattern; Amazon forest; Soil nutrients; Análisis de correspondencia canónica; K Ripley’s; Patrón punto espacial; Los bosques del Amazonas; Nutrientes del suelo